A systematic study of maghemite/PMMA nano-fibrous composite via an electrospinning process: Synthesis and characterization - Khanlou, H.M.; Ang, B.C.; Talebian, S.; Barzani, M.M.; Silakhori, M.; Fauzi, H. (Elsevier, 2015)
In this study, maghemite/PMMA nano-fibrous composites have been successfully fabricated by using the electrospinning process. PMMA nano-fibres have been selected to be used as the matrix; the PMMA was dissolved in three diverse solvents (Acetone, THF and DMF) in order to obtain fine PMMA nano-fibres. As a result, the PMMA-DMF proved to be the most appropriate polymer solution among the three solvents, with its impressive defect-free surface morphology results. The production of maghemite using Massart's procedure resulted in nano-particles with an average diameter of 4.98 +/- 0.13 nm (using transmission electron microscopy (TEM)). Maghemite nano-particle were then mixed with a prepared polymer solution in order to fabricate maghemite/PMMA nano-fibrous composite. Furthermore, the investigation of the morphology and structure of the composite was carried out using field emission scanning electron microscopy (FESEM), Energy-dispersion X-ray spectroscopy (EDX), Alternating Gradient Magnetometer (AGM), Fourier transform infrared spectrometer (FTIR), X-ray diffraction (XRD) and tensile strength measurement devices. The results indicated that there was a great amount of maghemite, both in and on the composite's surface, which can be utilized in the purpose of magnetic applications. (C) 2015 Elsevier Ltd. All rights reserved.